(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2026)
River Gomti is one of the major rivers in the northern Indian state of Uttar Pradesh. It flows through the fertile plains of Uttar Pradesh, serving as a lifeline for millions of people along its course. The river has significant cultural, historical, and ecological importance, deeply embedded in the heritage of the region. In terms of ecology, the Gomti River supports a rich ecosystem that flourishes in and around its waters recognitions to its various flora and fauna.Water Quality Indexing of the Gomti River from its origin to its confluence with the Ganga River has become increasingly crucial due to rising pollution levels and urbanization impacts. This study employs geospatial techniques and comprehensive water quality analysis to assess the river health across its entire stretch. Total 39 water samples were collected from multiple monitoring stations strategically located from the river’s origin at Gomat Taal (Pilibhit) to its confluence point with the Ganga River at kaithi (Ghazipur). The analysis incorporated key physicochemical parameters including dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total dissolved solids (TDS), pH and electrical conductivity. Geographic Information System (GIS) tools were utilized to create spatial distribution maps of water quality parameters and calculating Water Quality Index (WQI) values. Results indicated significant spatial variations in water quality, with deteriorating conditions observed in urban segments, particularly near Lucknow. The study revealed that approximately 45% of the river stretch falls under the ‘poor’ to ‘very poor’ water quality categories, primarily due to untreated sewage discharge and industrial effluents. This research provides crucial baseline data for river management authorities and highlights areas requiring immediate intervention for pollution control and ecosystem restoration.